Impact of branding on consumer buying behavior towards Samsung Smart Phone / Mohd Sharizami Mohd Rohari - Mohd Rohari, Mohd Sharizami (Faculty of Business and Management, 2018)
Branding is an image for a business where they were used by the consumer as perception towards the brand. The purpose of this study is to investigate the impact of branding on consumer buying behavior towards Samsung smart phone. Advertisement, brand image, brand association and brand loyalty are the characteristics of consumer buying behavior that used in this study. This study was conducted in Bandaraya Melaka by using purposive sampling technique. Data were collected from 100 respondents by using structured questionnaire and Statistical Package for the Social Sciences (SPSS) were used to analyze the results. The results shows that advertisement, brand image, brand association and brand loyalty have positive relationships with consumer buying behavior. Moreover, the variable that gives the most impact towards consumer buying behavior is brand association. Based on this study, there were some recommendation that has been made for the company and the future researcher.